2021
DOI: 10.4102/phcfm.v13i1.2948
|View full text |Cite
|
Sign up to set email alerts
|

Re-imagining health professions education in the coronavirus disease 2019 era: Perspectives from South Africa

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic hit South Africa in March 2020, severely disrupting health services and health education. This fundamentally impacted the training of future health professionals and catalysed a significant response from across the health education sector. In 2020, the South African Association of Health Educationalists requested members to submit reflections on different aspects of their COVID-19 related educational responses.Responding to the pandemic: Seven vignet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
9
2
Order By: Relevance
“…Learners in Y2 were more likely to be female and from more diverse cadres than learners in Y1. These findings are in contrast with other data highlighting how the COVID-19 pandemic revealed and increased pre-existing inequities in professional development opportunities for healthcare professionals in LMICs,(2, 18, 19) Although many health professions training institutions in SSA lack access and capacity to use digital technologies to deliver HIV training(20) our results affirm the critical role that online training interventions can play in advancing professional development opportunities especially for those healthcare professions historically underserved by capacity building interventions. (21)…”
Section: Discussioncontrasting
confidence: 99%
“…Learners in Y2 were more likely to be female and from more diverse cadres than learners in Y1. These findings are in contrast with other data highlighting how the COVID-19 pandemic revealed and increased pre-existing inequities in professional development opportunities for healthcare professionals in LMICs,(2, 18, 19) Although many health professions training institutions in SSA lack access and capacity to use digital technologies to deliver HIV training(20) our results affirm the critical role that online training interventions can play in advancing professional development opportunities especially for those healthcare professions historically underserved by capacity building interventions. (21)…”
Section: Discussioncontrasting
confidence: 99%
“…Another limitation is that this study did not consider the costs of training required to introduce OE. Although the coronavirus disease 2019 pandemic has demonstrated that it is possible to conduct clinical training remotely, 36 health facilities may not have access to the necessary bandwidth and computers present in a university environment. 36 Therefore, the cost of introducing OE should be assessed given the challenges with remote learning, especially in rural settings.…”
Section: Discussionmentioning
confidence: 99%
“…Teletraining and telepractice have not been employed extensively (Khoza-Shangase et al, 2021 ). The COVID-19 outbreak therefore brought to light the need for a paradigm shift in the manner in which clinical training for SLH in South Africa is viewed and conducted (Chin et al, 2021 ; Khoza-Shangase et al, 2021 ; Schmutz et al, 2021 ). In pursuit of solutions during ERTL, application of simulations was presented as one of the ways students can conduct their clinical training (Tabatabai, 2020 ).…”
Section: Introductionmentioning
confidence: 99%